Amylase, Phosphate, Zinc & Magnesium Serum Levels in Women with Toxoplasmosis - A. Abrahem, Sarra; A. Ibrahim, Suhad; Y. Hashim, Maryam (Al-Nahrain Journal of Science, 2025)
Toxoplasmosis has a significant infection rate in several Arab countries, such as Iraq. The role of the amylase enzyme and some trace elements, such as phosphorus (P), zinc, and magnesium, was evaluated with the incidence of toxoplasmosis in 80 Iraqi women (50% fertile and 50% infertile). Samples were collected from eighty blood infertile women (as patients, P group) and fertile women who were apparently healthy (as controls, C group), with an age range of 20-40 years. Each group was subdivided into two groups: with seropositive toxoplasma gondii IgG group (PP, and PC for patient and control group, respectively) and seronegative toxoplasma gondii IgG (NP, and NC for patient and control group, respectively). Amylase enzyme activity, phosphorus (P), zinc, and magnesium were estimated in the sera of women for each collected sample. There was a decrease in amylase level in positive and negative patients compared with healthy patients. The zinc level in fertile patients was significantly higher (P<0.05), while it was lower in positive patients compared to the C groups. The magnesium level increased significantly in positive patients (P<0.05) compared to the C groups. However, the magnesium level in patients with negative patients compared to healthy controls was non-significantly lower (P>0.05). Phosphorus level increased significantly (P<0.05) in positive patients compared to C groups. Changes in the level of the Amylase enzyme and the elements such as zinc, phosphorus, and magnesium can be considered indicators of the causes of toxoplasmosis.